2016
DOI: 10.1515/jpm-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine increases fetoplacental perfusion

Abstract: Although nifedipine had no effect on the PI, the RI or the S/D, it increased the mean pressure gradient, the VTI and FPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In a previous study on nifedipine and fetoplacental perfusion, nifedipine is shown to increase fetoplacental perfusion 19 . However, there was no control group in this study for a comparison to be made.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a previous study on nifedipine and fetoplacental perfusion, nifedipine is shown to increase fetoplacental perfusion 19 . However, there was no control group in this study for a comparison to be made.…”
Section: Discussionmentioning
confidence: 80%
“…There are a limited number of studies that evaluate the effects of maternal nifedipine treatment on fetoplacental blood flow in maternal uterine arteries and fetal umbilical arteries. Some studies demonstrate that the maternal uterine artery and fetal umbilical artery RI values did not change significantly 48 hours after nifedipine treatment, but some studies indicate that the uterine artery RI values did change significantly 11 19 20 . Such a difference may be due to the use of different doses of nifedipine in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our data showed that nifedipine tocolysis produced no differences in the umbilical arteries Doppler (RI and PI) or in the MCA to umbilical artery ratio, similar to the findings of Karahanoglu et al who found that RI, the PI and the S/D ratio of UA did not change after treatment with nifedipine. 18 Also, de Heus et al showed that over the 5-day study period. The use of tocolytics did not significantly alter the time courses of PI-values for UA (p=0.37).…”
Section: Discussionmentioning
confidence: 99%
“…The results of some authors have shown that chronic hypertension in pregnant women does not increase the risk of the occurrence of FGR [6]. Furthermore, calcium channel blockers have been identified as predictors of SGA in some studies [7], whereas no statistically significant association has been found between calcium channel blocker use during pregnancy and low birth weight infants in another study [8]. In light of these unknowns and the great clinical significance of the problem of FGR and SGA newborns, the aim of our study was to identify risk factors that contribute to the occurrence of FGR and SGA and quantify the strength of their impact.…”
Section: Introductionmentioning
confidence: 99%